Law on Display : the Digital Transformation of Legal Persuasion and Judgment. - Feigenson, Neal (Ex Machina: Law, Technology and Society Series., 2009)
Experience the multimedia and view the links featured in the book at lawondisplay.com. Visual and multimedia digital technologies are transforming the practice of law: how lawyers construct and argue their cases, present evidence to juries, and communicate with each other. They are also changing how law is disseminated throughout and used by the general public. What are these technologies, how are they used and perceived in the courtroom and in wider culture, and how do they affect legal decision making?. In this comprehensive survey and analysis of how new visual technologies are transforming.